ANALYSIS OF POTENTIAL HAZARDS FOR PALM OIL MILL PRODUCTION WORKERS USING THE (HIRARC) METHOD IN PT. X - Utami, Tri Niswati; Ashifa, Mutiara; Siregar, Yusuf Syahputra; Fauziah, Ella Asri; Salsabila, Fatma; Nasution, Priska Karina; Fadilah, Nurly (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
The production process in palm oil mills is inseparable from potential hazards in the workplace such as the FFB Receiving Station area (Scales, Sorting/Loading ramp), then the Boiling Station (Sterilizer), the Grinding Station (Threshing/Theresser/autofeeder), the Felt/Pumping Station (Screw Press, Slamming Station, Clarification Station, CPO Storage Tank (Storange Tank), Boiler Station and Engine Room Station (Power House), Demint Plant Station. Efforts that can be made are by conducting risk management through the identification of potential occupational safety and health hazards, using the HIRARC method. The goal of HIRARC is to recognize potential hazards and various operational problems in each process. Based on the risk assessment, there are four categories of risk levels identified, namely risk levels, namely Low Risk, Modarate Risk, High Risk, and Extreme Risk. The risk rating provides a level for each risk category, which results in the most dangerous risk, namely the Stockpile Tank Station and Engine Room get a level of 15 High Risk, then at the Boiling, Slamming, Clarification, Steam Boiler Station get a level of 12 High Risk. Risk Control that must be carried out on potential hazards at PT. X is Required to Wear Complete PPE that has been given (gloves, anti-slip shoes, mask, ear plug/ear, helmet, safety glasses), Obey signs, Work according to SOPs and Work instructions, clean the workplace area, monitor to work according to procedures, Carry out periodic Maintanetance, and the author hopes that at PT. X establishes new policies and regulations for workers by providing penalties such as issuing first warning letters or fines for workers who do not comply with SOPs and do not wear PPE. Instead, appreciation is given to workers who comply with SOPs and use PPE properly and correctly.